Exposure to maternal obesity programs sex differences in pancreatic islets of the offspring in mice - Nicholas, Lisa M. (Diabetologia, 2019)
AIMS/HYPOTHESIS: Obesity during pregnancy increases offspring type 2 diabetes risk. Given that nearly half of women of child-bearing age in many populations are currently overweight/obese, it is key that we improve our understanding of the impact of the in utero/early life environment on offspring islet function. Whilst a number of experimental studies have examined the effect of maternal obesity on offspring islet architecture and/or function, it has not previously been delineated whether these changes are independent of other confounding risk factors such as obesity, postnatal high-fat-feeding and ageing. Thus, we aimed to study the impact of exposure to maternal obesity on offspring islets in young, glucose-tolerant male and female offspring. METHODS: Female C57BL/6J mice were fed ad libitum either chow or obesogenic diet prior to and throughout pregnancy and lactation. Offspring were weaned onto a chow diet and remained on this diet until the end of the study. An IPGTT was performed on male and female offspring at 7 weeks of age. At 8 weeks of age, pancreatic islets were isolated from offspring for measurement of insulin secretion and content, mitochondrial respiration, ATP content, reactive oxygen species levels, beta and alpha cell mass, granule and mitochondrial density (by transmission electron microscopy), and mRNA and protein expression by real-time RT-PCR and Western blotting, respectively. RESULTS: Glucose tolerance was similar irrespective of maternal diet and offspring sex. However, blood glucose was lower (p < 0.001) and plasma insulin higher (p < 0.05) in female offspring of obese dams 15 min after glucose administration. This was associated with higher glucose- (p < 0.01) and leucine/glutamine-stimulated (p < 0.05) insulin secretion in these offspring. Furthermore, there was increased mitochondrial respiration (p < 0.01) and density (p < 0.05) in female offspring of obese dams compared with same-sex controls. Expression of mitochondrial and nuclear-encoded components of the electron transport chain, L-type Ca(2+) channel subtypes that play a key role in stimulus-secretion coupling [Cacna1d (p < 0.05)], and oestrogen receptor α (p < 0.05) was also increased in islets from these female offspring of obese dams. Moreover, cleaved caspase-3 expression and BAX:Bcl-2 were decreased (p < 0.05) reflecting reduced susceptibility to apoptosis. In contrast, in male offspring, glucose and leucine/glutamine-stimulated insulin secretion was comparable between treatment groups. There was, however, compromised mitochondrial respiration characterised by decreased ATP synthesis-driven respiration (p < 0.05) and increased uncoupled respiration (p < 0.01), reduced docked insulin granules (p < 0.001), decreased Cacna1c (p < 0.001) and Cacna1d (p < 0.001) and increased cleaved caspase-3 expression (p < 0.05). CONCLUSIONS/INTERPRETATION: Maternal obesity programs sex differences in offspring islet function. Islets of female but not male offspring appear to be primed to cope with a nutritionally-rich postnatal environment, which may reflect differences in future type 2 diabetes risk. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-019-05037-y) contains peer-reviewed but unedited supplementary material, which is available to authorised users.